Notes on Hexapodidae (Crustacea, Brachyura) from Indonesia and Malaysia, with description of a new species of Mariaplax Rahayu & Ng, 2014, from Lombok, Indonesia - Ng, Peter K. L.; Rahayu, Dwi Listyo (Zootaxa, 2015)
The male of Hexapinus latipes (De Haan, 1835), so far known only from female specimens, is described based on the material reported by De Man (1888) as “Hexapus sexpes”. Material referred to “Hexapus sexpes” by Tesch (1918) is shown instead to belong to Hexapinus simplex Rahayu & Ng, 2014, and Hexapinus latus Rahayu & Ng, 2014, while his “Hexaplax megalops Doflein, 1904” belongs to Hexaplax aurantium Rahayu & Ng, 2014. A new species, Mariaplax aspera n. sp., is described from a female collected in Lombok, Indonesia. This new species most closely resembles M. narusei Rahayu & Ng, 2014, described from Japan, but differs by its relatively narrower carapace, shorter ambulatory legs, tuberculated third maxillipeds, and shorter telson.